HYPNOTIC SELLING MARKETING COMMUNICATION STRATEGY (CASE STUDY OF HOUSING MARKETING IN KEDATON HOMES SEMARANG) - Pracelia ongko Wijaya; Hardiyarso Hardiyarso; Setyowati Setyowati; Rotuniar Pasaribu (Universitas Katolik Soegijapranata, 2022)
Marketing communication is a process between a seller to a buyer by a mutually beneficial reciprocal exchange between both two parties in which the company gets a selling value such as profit or income and consumers get the desired goods needs. Practically, marketing communication requires a suggestive communication strategy. Someone or communicator who can convey, inform, and provide the information needed to consumers, namely sales marketing. This research focused on sales marketing who works in a housing products company in the BSB City area. In this study, sales marketing at the Kedaton Homes, BSB City housing became the subject of research as informants totalling four (4) people with two sales marketing who had worked for one year and 2 sales marketing who had worked for less than six months. One of the suggestive marketing strategies implemented by sales marketing in Kedaton Homes is hypnotic selling. Hypnotic selling is one of the suggestive communication strategies with the art of speaking and conveying something enchantingly to the consumers. This research on hypnotic selling aims to determine the application of hypnotic selling communication strategies to marketing in Kedaton Homes. The research method used is a qualitative research method with data analysis based on interviews, observations and documentation to obtain the validity and clarity of the data. This study used the theory of Willy Wong (2010) in his book entitled ‘hypnosis for selling’. The results in this study indicated that the application of the hypnotic selling communication strategy applied by sales marketing at Kedaton Homes had similar results in accordance with the theory presented by Willy Wong with several points sorted such as the application of initial suggestive selling, advance suggestive selling and final suggestive in the form of closing which affect the target marketing every months.